A framework to analyze the dynamics of the socioeconomic metabolism of countries: A Portuguese case study. - Cunha, Sónia; Ferrão, Paulo (Journal of Industrial Ecology, 2021)
Socioeconomic metabolism dynamics are relevant to identify (un)sustainable development pathways in different economies, particularly if the evolution of resource productivity of critical economic sectors can be quantified. This paper offers a four‐step methodological framework to quantify these dynamics for an economy in a way that can be replicated for a series of years and countries. This methodological framework is based on the compilation of economic and physical flows in the form of input‐output tables in a time series, making use of publicly available data. The data download and processing were automatized using Python, creating an expedited analysis process. The results characterize the flows through and within a country and allow the user to identify structural changes in the economy by tracking both monetary and physical flows for 17 material groups and up to 37 economic sectors. The application of the methodological framework is illustrated in a case study covering the 2008 economic crisis in Portugal, in which the socioeconomic metabolism, the underlying structural changes, and the corresponding environmental impacts are characterized. The use of this information for the design of decoupling policies is discussed, in view of promoting sustainable dematerialization during periods of economic prosperity.